Teaching-Presence through the Lens of Performativity in the Postdigital Age - Sun, Yixuan (Proceedings of the International Conference on Networked Learning, 2026)
Digital and physical learning environments continuously interact. Teaching is conceptualized not just as “doing” but as an embodied performance that constructs reality. This study explores how Chinese university English teachers perceive and manage student presence and engagement in postdigital classrooms. Framed by the theory of performativity, the research investigates how digital platforms shape teacher-student interactions and pedagogical authority. It addresses two central questions: How do teachers interpret student presence in mediated online spaces, and what strategies do they use to navigate the challenges of these interactions? Adopting a case study approach, this research draws on in-depth interviews with three university English teachers from a liberal arts institution in Beijing. The participants who represent different age groups all had extensive experience with blended teaching, providing rich, practical insights. These three participants are chosen from a larger dataset. A thematic analysis of the interview data was made to identify key patterns in their experiences. The findings revealed differences in how teachers understand online presence. Their understandings ranged from requiring visual confirmation via cameras, to asking for auditory participation, to accepting text-based responses in the chatroom as sufficient. The study shows that these different understandings lead to different teaching strategies. There are three main patterns: some teachers treat the screen like a window into the classroom, others struggle with students who are physically online but mentally absent, and many face a new power dynamic where students’ control over their cameras and mics can challenge the teacher’s authority. In conclusion, the study shows that “presence” in today’s blended classrooms is a complicated idea, shaped by technology, school rules, and the unique relationship between each teacher and student. The findings highlight that to build a real sense of connection, teachers need to be flexible and understanding, rather than just tracking who is logged in. These insights contribute to understanding how to develop more effective and embodied teaching practices in postdigital education. Future research could include a greater number of participants with broader identity, as well as observe online classes over a longer period to provide an even clearer and more detailed picture of these interactions.